2018
DOI: 10.1088/2040-8986/aaa2c5
|View full text |Cite
|
Sign up to set email alerts
|

Solar selective performance of metal nitride/oxynitride based magnetron sputtered thin film coatings: a comprehensive review

Abstract: Since solar thermal collectors are considered to be the most direct way of converting the solar energy into the usable form, in the last few years growing attention has been paid to the development of transition metal nitride and metal oxynitride based thin film selective surfaces for solar-thermal collectors in order to harvest more solar energy. A solar-thermal energy system, generally, shows very high solar absorption of incident solar radiation from the solar-thermal collectors in the visible range (0.3 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 126 publications
0
9
0
Order By: Relevance
“…Many studies have been undertaken which examine the structural, morphological, spectral selective, local electronic bonding states, optical, mechanical and tribological properties of CrN-based thin film coatings [31][32][33][34][35][36][37]. However, a comprehensive study investigating the impact of annealing temperatures on structural, morphological, and optical properties and providing a detailed mechanical analysis via experimental procedure and finite element modeling in one paper is still lacking.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Many studies have been undertaken which examine the structural, morphological, spectral selective, local electronic bonding states, optical, mechanical and tribological properties of CrN-based thin film coatings [31][32][33][34][35][36][37]. However, a comprehensive study investigating the impact of annealing temperatures on structural, morphological, and optical properties and providing a detailed mechanical analysis via experimental procedure and finite element modeling in one paper is still lacking.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…cristia, Rosa ards rovar, Pereskia bleo, and Alternanthera ficoidea. These defect bands generate an energy tail that extends from both the bottom of the conduction bands and top of the valence bands to the deep of the bandgap [58,59]. This energy correlated defect tail is termed as the Urbach energy provided by Eq.…”
Section: Fourier Transform Infrared (Ftir) Spectroscopymentioning
confidence: 99%
“…Some high-temperature solar absorber coatings that have already been reported are CrAlN/CrAlON/Al 2 O 3 , CrAlN/CrAlON/Si 3 N 4 , Ti/AlTiN/AlTiON/AlTiO, TiN/AlCrSiO/AlCrSiO, AlMoN­(H)/AlMoN­(L), Mo–Si 3 N 4 , Mo/ZrSiN/ZrSiON/SiO 2 , W/Ag/WN-AlN/AlN/SiO 2 , W/AlSi x N/AlSiO y N x /AlSiO x , W/CrAlSiN x /CrAlSiN x O y /SiAlO x , and W/WAlSiN/SiON/SiO 2 . In addition, a table presenting the solar selectivity of metal nitride/oxynitrides SSC coatings deposited by magnetron sputtering on various substrates can be found in ref . In previous works, Escobar-Galindo et al studied the microstructure, element composition, chemical bonding, and optical properties of Al y Ti 1– y (O x N 1– x ) multilayered coatings, both before and after single-stage (12 h) and thermal cycles in air. , The findings revealed that the SSCs remained stable up to 650 °C during the single-stage tests.…”
Section: Introductionmentioning
confidence: 99%